1998
DOI: 10.1016/s0735-1933(98)00015-3
|View full text |Cite
|
Sign up to set email alerts
|

Particulate viscous effects on the compressible boundary-layer two-phase flow over a flat plate

Abstract: The problem of compressible boundary-layer laminar flow of a particulate suspension over a semi-infinite fiat plate is solved numerically using the finite-difference methodology. The mathematical model employed includes such effects as particle-phase viscous stresses, variable position-dependent particle slip coefficient, and general power-law viscositytemperature and thermal conductivity-temperature relations• Graphical results for the displacement thicknesses, skin-friction coefficients, and the wall heat tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Both fluid-particle phases are also assumed to behave as interacting continua. Besides, the interaction between the solid particles and the fluid is described by the Stokes linear drag HFF 28,6 force and other possible interactions such as the virtual force, the shear lift force and the spin-lift force will be ignored (Chamkha, 1998).…”
Section: Problem Formulationmentioning
confidence: 99%
“…Both fluid-particle phases are also assumed to behave as interacting continua. Besides, the interaction between the solid particles and the fluid is described by the Stokes linear drag HFF 28,6 force and other possible interactions such as the virtual force, the shear lift force and the spin-lift force will be ignored (Chamkha, 1998).…”
Section: Problem Formulationmentioning
confidence: 99%
“…The dust particles are assumed to be spherical in shape and uniform in size, and the number density of the dust particle is taken as a constant throughout the flow. The basic boundary layer equations of the two-HFF 27,4 dimensional flow in the usual notations are (Hamdan and Barron, 1990;Chamkha, 1998;Ramesh and Gireesha, 2013) as follows:…”
Section: Problem Formulationmentioning
confidence: 99%
“…Again, due to the presence of dust particles, the fluid phase surface heat transfer decreases, which was studied by Chamkha. 7 Misra and Tripathy 8 investigated the effect of electrification of particles in the modeling of boundary layer flow on the top of a horizontal flat plate and observed that particles move faster with increasing temperature. Again, heat transfer from the fluid to plate is always carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The solution is valid through the whole length of the plate and heat flow occurs from plate to fluid throughout the region. From the literature, [1][2][3][4][5][6][7][8][9][10][11][12] it is clear that the flow characteristics are significantly affected by the presence of dust particles and, hence, boundary layer flow analysis with a suspension of particles draws much more attention at the present time. Again, the heat transfer analysis in boundary layer flows along a continuously stretching surface with a buoyant force focused on industrial areas and many manufacturing processes, such as hot rolling and paper industries, cooling of metallic sheets, and aerodynamics extrusion of plastic sheets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation